Weekend effect in acute coronary syndrome: A meta-analysis of observational studies. Issue 5 (August 2019) - Kwok, Chun Shing; Al-Dokheal, Mohammed; Aldaham, Sami; Rushton, Claire; Butler, Rob; Kinnaird, Tim; Zaman, Azfar; Zaman, M Justin; Timmis, Adam; Mamas, Mamas A
Background: The effect of a weekend compared with a weekday hospital admission on patient outcomes after an acute coronary syndrome is unclear. This study aims to determine whether collectively there is a weekend effect in acute coronary syndrome. Method: We conducted a systematic review and meta-analysis of cohort studies examining the association between weekend compared to weekday admission at any time of the day and early mortality (in-hospital or 30-day). A search was performed on Medline and Embase and relevant studies were pooled using random effects meta-analysis for risk of early mortality. Additional analyses were performed considering only more recent studies (conducted after 2005) and by patient group (ST-elevation myocardial infarction [STEMI] or non-STEMI [NSTEMI]), as well as meta-regression according to starting year and mean year of study. Results: A total of 18 studies were included with over 14 million participants incorporating 3 million weekend and over 11.5 million weekday admissions and the rates of mortality were 19.2% and 23.4%, respectively. The pooled results of all 18 studies suggest that weekend admission was associated with a small increased risk of early mortality (odds ratio [OR] 1.06, 95% confidence interval [CI] 1.03–1.09). The results for subgroups of STEMI and NSTEMI cohorts were not statistically significant and timing of admission after 2005 had minimal influence on the results (OR 1.06, 95% CI 0.95–1.17). Conclusions: There is a small weekend effect for admission with acute coronary syndrome that has persisted over time.